Eco – Wudu’: Sustainable Watering System by Using Wudu Water - Nik Erfan Haffey Nik Man; SITI ASMAHANI MOHAMED (Nusantara Civil Engineering Journal, 2026)
The Eco-Wudu Sustainable Watering System project was developed to address the issue of wasting clean wudu water at the Polytechnic surau. This study was conducted because the amount of water used for ablution daily is high, and most of it is discharged directly into the drain without being reused. The main problem to be solved is the lack of an efficient water management system to recycle ablution water for other purposes, such as plant irrigation. The approach used in this project involves the development of an automatic prototype system that functions to collect and reuse ablution water. The system consists of an Arduino Uno, soil moisture sensor, automatic water pump, storage tank, uPVC gutter channel, and a solar panel as a green energy source. Data were collected through tests on water flow rate, soil moisture levels, and the amount of water saved before and after the project implementation. The findings show that the system operates effectively in automatically controlling irrigation when the soil reaches a certain level of dryness, thereby reducing the use of main water supply and improving energy efficiency. The analysis revealed a significant amount of water savings compared to the previous manual method. In conclusion, this project not only contributes to green engineering practices and sustainable water management but also adds value to the surau community by fostering environmental awareness. For future studies, improvements can be made by integrating a more advanced water filtration system and connecting the system to an IoT-based database for real-time monitoring. Keywords: Smart Irrigation System; Recycled Ablution Water; Arduino; Solar Energy; Absolute Error; Standard Deviation;